2013
DOI: 10.1002/bit.24872
|View full text |Cite
|
Sign up to set email alerts
|

Dual factor delivery of CXCL12 and Exendin‐4 for improved survival and function of encapsulated beta cells under hypoxic conditions

Abstract: A bioartifical pancreas (BAP) remains a promising approach for treating insulin-dependent diabetes. Several obstacles to the clinical implementation of a BAP remain, including hypoxia following implantation. Within native pancreatic islets, CXCL12 and glucagon-like peptide-1 (GLP-1) act in a paracrine fashion to promote the survival, function, and proliferation of β-cells. This work sought to investigate if the presentation of CXCL12 and delivery of a GLP-1 receptor analog, Exendin-4 (Ex-4), alone and in combi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 56 publications
1
14
0
Order By: Relevance
“…Our RT-qPCR results showed significantly increased transcription of both receptor genes after islet incubation with CXCL12α, targeting CXCR4 as the most important receptor responsible for signaling within the islet. This is in accordance with previous reports indicating that CXCL12 is involved in the regulation of insulin secretion [89]. β-cell injury induces CXCL12 expression and the secreted CXCL12 causes dedifferentiation of adjacent -cells into pro-α-cells, which are further transformed into pancreatic β-cells [18,90].…”
Section: Cxcl12α Signaling Influences the Expression Of Voltage-gatedsupporting
confidence: 93%
“…Our RT-qPCR results showed significantly increased transcription of both receptor genes after islet incubation with CXCL12α, targeting CXCR4 as the most important receptor responsible for signaling within the islet. This is in accordance with previous reports indicating that CXCL12 is involved in the regulation of insulin secretion [89]. β-cell injury induces CXCL12 expression and the secreted CXCL12 causes dedifferentiation of adjacent -cells into pro-α-cells, which are further transformed into pancreatic β-cells [18,90].…”
Section: Cxcl12α Signaling Influences the Expression Of Voltage-gatedsupporting
confidence: 93%
“…Exenatide, a GLP‐1 receptor agonist, is a clinically approved synthetic version of Ex4 used to treat type 2 diabetes. As a GLP‐1 receptor agonist, Ex4 may stimulate insulin secretion and β cell replication and reduce apoptosis after transplant . Initial approaches using Ex4 to enhance islet transplantation involved treating islets prior to transplantation .…”
Section: Discussionmentioning
confidence: 99%
“…Herein, we investigate the localized delivery of exendin‐4 (Ex4) or insulin‐like growth factor‐1 (IGF‐1) at the implantation site as a means to enhance islet engraftment and function. Ex4 is a potent and long‐acting glucagon‐like peptide‐1 (GLP‐1) receptor agonist that stimulates glucose‐dependent insulin secretion and islet cell replication, protects against apoptosis and improves outcomes in islet transplant models . IGF‐1 is a growth factor that decreases apoptosis , stimulates cellular growth and proliferation, and is involved in regulating islet beta cell mass, proliferation and regeneration .…”
Section: Introductionmentioning
confidence: 99%
“…. With regard to homing, it has been reported that DPP‐4 inhibitors can enhance HSCs migration towards chemokine (C‐X‐C motif) ligand 12 (), which plays an important role in pancreatic development and β ‐cell function and survival . A potential treatment for T1DM may involve the combination of DPP‐4 inhibitors and UCB HSCs transplantation.…”
Section: Umbilical Cord Blood‐derived Stem Cellsmentioning
confidence: 99%
“…Some efforts have been made to expand UCB HSCs in vitro with some preliminary success.. 89,90 With regard to homing, it has been reported that DPP-4 inhibitors can enhance HSCs migration towards chemokine (C-X-C motif) ligand 12 (CXCL12), 91,92 which plays an important role in pancreatic development and β-cell function and survival. 93 A potential treatment for T1DM may involve the combination of DPP-4 inhibitors and UCB HSCs transplantation. Although the AHSCT trials suggest that patients with adequate residual β-cells achieved insulin independence, the response could not be maintained in most patients.…”
Section: Hematopoietic Stem Cellsmentioning
confidence: 99%